2000
DOI: 10.1046/j.1365-2699.2000.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeovegetation of China: a pollen data‐based synthesis for the mid‐Holocene and last glacial maximum

Abstract: International audiencePollen data from China for 6000 and 18,000 C-14 yr BP Were compiled and used to reconstruct palaeovegetation patterns, using complete taxon lists where possible and a biomization procedure that entailed the assignment of 645 pollen taxa to plant functional types. A set of 658 modern pollen samples spanning all biomes and regions provided a comprehensive test for this procedure and showed convincing agreement between reconstructed biomes and present natural vegetation types, both geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
306
5
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 376 publications
(332 citation statements)
references
References 25 publications
16
306
5
2
Order By: Relevance
“…S1b). However, the climatic changes of the Quaternary have caused repeated shifts in the distribution of forests and understorey species throughout East Asia (Liu, 1988;Yu et al, 2000;Qiu et al, 2011). With the increasing temperature since the LGM, the predicted suitable habitats of C. cathayanum, C. giganteum and C. giganteum var.…”
Section: Response To Climatic Change and Implications For Conservationmentioning
confidence: 99%
“…S1b). However, the climatic changes of the Quaternary have caused repeated shifts in the distribution of forests and understorey species throughout East Asia (Liu, 1988;Yu et al, 2000;Qiu et al, 2011). With the increasing temperature since the LGM, the predicted suitable habitats of C. cathayanum, C. giganteum and C. giganteum var.…”
Section: Response To Climatic Change and Implications For Conservationmentioning
confidence: 99%
“…The C 4 species S. viridis and P. miliaceum were domesticated in North China, where the climate was arid, winters dry and cold, and summer rains unreliable (Yu et al, 2000). The C 3 species were also domesticated in dry climates.…”
Section: Implications For the Origin Of Agriculturementioning
confidence: 99%
“…NLRs were assigned based on Song et al (2004) and the taxa were grouped according to biome types listed in Yu et al (2000) and Ni et al (2010) (see Table 1), and filtered for pollen taxa found in the Eocene record of Xining. Subsequently 6 biome types were assigned based on more general versions of the PFTs and biomes described by Yu et al (2000): 1) xerophytic vegetation (desert and steppe), 2) conifer forest, 3) temperate broad leaved forest, 4) warm broad leaved forest, 5) tropical forest, and 6) pteridophytes.…”
Section: Nearest Living Relatives (Nlr) and Coexistence Approach (Coa)mentioning
confidence: 99%
“…Subsequently 6 biome types were assigned based on more general versions of the PFTs and biomes described by Yu et al (2000): 1) xerophytic vegetation (desert and steppe), 2) conifer forest, 3) temperate broad leaved forest, 4) warm broad leaved forest, 5) tropical forest, and 6) pteridophytes. Taxa that did not fit these groups were placed in a group labeled 'other taxa'.…”
Section: Nearest Living Relatives (Nlr) and Coexistence Approach (Coa)mentioning
confidence: 99%
See 1 more Smart Citation